A MODERN APPROACH TO FUTURE SURDOPEDAGOGS IN THE PROCESS OF INDEPENDENT EDUCATION (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Through independent education is a type of educational work for students; it creates the basis for the acquisition of life skills, social and professional attractiveness, personal capabilities and self-esteem, and contributes to the formation of student independence as a human virtue.